Dual Trigger for Final Follicular Maturation Improves Cumulative Live-Birth Rate in Ovarian Stimulation for Freeze-All In Vitro Fertilization/Intracytoplasmic Sperm Injection Cycles - Zhu, Haiyan; Zhao, Chenqiong; Pan, Yibin; Zhou, Hanjing; Jin, Xiaoying; Xu, Wen; Zhang, Songying (Frontiers in Endocrinology, 2021)
Study Question Does dual trigger in freeze-all in vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI) cycles improve the cumulative live-birth outcome compared with human chorionic gonadotropin (hCG) trigger? Summary Answer Dual trigger for final follicular maturation improves the cumulative pregnancy and live-birth rates compared with hCG trigger in freeze-all IVF/ICSI cycles. What Is Known Already Dual trigger could increase the numbers of oocytes and mature oocytes and improve pregnancy rates. Study Design, Size, Duration This retrospective cohort analysis included data from 4438 freeze-all IVF/ICSI cycles between January 2012 and December 2017. Participants/Materials, Setting, Methods Women aged 20−49 years who underwent ovarian stimulation and oocyte retrieval for autologous IVF/ICSI with a freeze-all policy in our centre were enrolled. Data on number of oocytes retrieved, number of mature oocytes, clinical pregnancy rate, live-birth rate, cumulative pregnancy rate, and cumulative live-birth rate (CLBR) were assessed and compared between patients who underwent a dual trigger and hCG trigger. Multivariate logistic regression was performed to identify and adjust for factors known to independently affect the CLBR. Main Results and the Role of Chance A total of 4438 IVF/ICSI cycles were analyzed, including 1445 cycles with single hCG trigger and 2993 cycles with dual trigger. The cumulative biochemical pregnancy rate (60.8% vs. 68.1%, P<0.001; odds ratio (OR): 0.727; 95% confidence interval (CI): 0.638–0.828), cumulative clinical pregnancy rate (52.9% vs. 58.5%, P<0.001; OR: 0.796; 95%CI: 0.701–0.903), and CLBR (44.3% vs. 50.5%, P<0.001; OR: 0.781; 95%CI: 0.688–10.886) were all significantly lower in the hCG-trigger group compared with the dual-trigger group. The clinical pregnancy rate (48.2% vs. 58.2%, P=0.002; OR: 0.829; 95%CI: 0.737–0.934) and embryo implantation rate (34.4% vs. 38.9%, P<0.001; OR: 0.823; 95%CI: 0.750–0.903) in each transfer cycle were also significantly lower in the hCG-trigger group compared with the dual-trigger group. After controlling for all potential confounding variables, the trigger method was identified as an independent factor affecting the CLBR. The OR and 95%CI for hCG trigger were 0.780 and 0.641–0.949 (P=0.013). Limitations, Reasons for Caution The data used to analyse the effect of dual trigger on cumulative pregnancy and live-birth outcomes were retrospective, and the results may thus have been subject to inherent biases. Further prospective randomized controlled trials are required to verify the beneficial effects of dual trigger. Wider Implications of the Findings Dual trigger had a positive effect on CLBRs, suggesting that it could be used as a routine trigger method in freeze-all cycles. Study Funding/Competing Interest(s) This study was supported by grants from National Key Research and Development Program of China (2018YFC1004800), the Natural Science Program of Zhejiang (LY19H040009), the National Natural Science Foundation of China (No. 81601236). No authors have competing interests to declare.